Bas Music Learning Strategy Based on CTL as a Strengthening of Student Character through Curricular Integration - Muh Arqam; Sumasno Hadi; Muhammad Budi Zakia Sani; Wahyu Pratama (PANTUN: Jurnal Ilmiah Seni Budaya, 2026)
This article explores the role of regional arts, particularly Bas traditional music, in supporting student character development through the application of Contextual Teaching and Learning (CTL). The study examines character-related values embedded in Bas musical practices and considers how these values can be integrated into learning activities. A qualitative approach with descriptive analysis was employed to interpret the educational potential of Bas traditional music within curricular contexts. The findings indicate that Bas music contains values associated with discipline, cooperation, responsibility, and appreciation of local culture. Within the CTL framework, these values appear to be engaged through contextual and experience-based learning processes in art practice. Learning activities such as project-based work, group discussion, and reflective exercises emerged as approaches that supported students’ engagement with character-related values. These findings suggest that the integration of Bas traditional music into CTL-based learning offers opportunities to connect character education with local cultural knowledge within educational settings.